Class Percentage of Students With Reading Difficulties on Content Knowledge and Comprehension. (March 2019) - Vaughn, Sharon; Fall, Anna-Mária; Roberts, Greg; Wanzek, Jeanne; Swanson, Elizabeth; Martinez, Leticia R.
We examined the efficacy of a content acquisition and reading comprehension intervention implemented in eighth-grade social studies classrooms. Using a within-teacher randomized control design, 18 eighth-grade teachers' social studies classes were randomly assigned to a treatment or comparison condition. Teachers taught all their classes (treatment and comparison) using the same content; however, in the treatment classes, teachers used instructional practices that included comprehension canopy, essential words, knowledge acquisition, and team-based learning. Students with reading comprehension difficulties in the treatment classes ( n = 359) outperformed students with reading comprehension difficulties in the comparison classes ( n = 331) on measures of content knowledge acquisition and content reading comprehension but not general reading comprehension. In addition, the proportion of students with reading comprehension difficulties in classes moderated outcomes for content knowledge acquisition and content reading comprehension.